Scenario Planning Development for PT Krakatau Steel (The Indonesian Journal of Business Administration, 2012)
The current business environment showing trends of many factors that relating to steel industry has dynamic changes that cannot be predicted only with linear forecasting method. Some of these, especially in external factors like political, economical, social, environmental, and technological has its impact and their level of uncertainties. The study objective is to develop scenarios to give an overview of the future market situation in Indonesian steel industry and all driving forces that have an impact to this industrial sector then used it as a tool to make any strategic decision for PT Krakatau Steel. As a leader in domestic steel market, PT Krakatau Steel, a State Own Enterprise steel company, now began to expand their business by making several strategic projects which marked with their decision to be a public company in 2010. With their momentum to prepare the future business environment, a study was conducted in PT Krakatau Steel in 2012 to analyzed their business issues and seek the major driving forces that have the most impact with high level of uncertainty to the firm. Three critical driving forces has been found as the axes of the uncertainty matrix in scenario planning, which is global steel price, government support, and realization of national economic development plans. By having scenarios, the firm can see both implications and options in future situation and aligned it with corporate strategic road map with monitoring process to see the shift of each scenario in their early warning signs. Keywords: Scenario Planning, Strategic Decision Making, Steel Industry, PT Krakatau Steel.